THE EFFECT OF TAXPAYER AWARENESS AND TAX SANCTIONS ON TAXPAYER COMPLIANCE IN PAYING LAND AND BUILDING TAX IN CIBIRU DISTRICT - Alsya Putri Saliha; Rachmat Hidayat (Jurnal Ekonomi, 2023)
The purpose of this research is to ascertain the impact of taxpayer education and tax penalties on taxpayer compliance with regard to paying land and building taxes. Comparative causal analysis is the study methodology used. People who are required to pay land and construction taxes make up the study subjects. Taxpayer awareness, tax penalties, and tax compliance are research factors. The independent variable is taxpayer knowledge and tax penalties, while the dependent variable is taxpayer compliance with regard to paying land and building taxes. 6,818 individuals who pay land and building taxes in Cibiru District make up the study's population. As many as 100 persons had their samples collected at random. Multiple linear regression is used to analyze data. The study's findings demonstrate that tax penalties and knowledge of taxpayers' rights separately have an impact on taxpayer compliance, and that awareness of taxpayers' rights and tax penalties together have an impact on taxpayer compliance.